2008
DOI: 10.1111/j.1471-0528.2008.02008.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel developments on cervical length screening and progesterone for preventing preterm birth

Abstract: Cervical length (CL) measured by transvaginal ultrasound is an effective screening test for the prevention of preterm birth (PTB). The criteria for an effective screening test are all met by CL. It studies an important condition (PTB); it is safe and acceptable by >99% of women; it recognises an early asymptomatic phase that precedes PTB by many weeks; it has a well-described technique, is reproducible, is predictive of PTB in all populations studies so far; and, perhaps most importantly, it has been shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 34 publications
2
29
1
Order By: Relevance
“…16,19,28,29,35 They reported that cervical length measurement by transvaginal ultrasonography is an accurate and valid method of measuring the cervix, 35 and may be a useful method of predicting who is at risk for preterm delivery. 16,19 This hypothesis turned out to be true with postconization patients. 28 The cervical length appears to be inversely proportional to the risk of preterm birth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,19,28,29,35 They reported that cervical length measurement by transvaginal ultrasonography is an accurate and valid method of measuring the cervix, 35 and may be a useful method of predicting who is at risk for preterm delivery. 16,19 This hypothesis turned out to be true with postconization patients. 28 The cervical length appears to be inversely proportional to the risk of preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…The mid-trimester cervical length was measured by ultrasonography between 14 to 28 gestational weeks based on previous studies. [16][17][18] Cervical length less than 2.5 cm was considered to be short. 16,19 Each conization specimen consisted of 1 to 3 fragments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The alignment of collagen varies from one layer to another with inner and outer layer having collagen arranged longitudinally, however middle layer has circumferentially aligned collagen [15,41,42]. As the cervix remodels for birth the cervix softens before the cervical length decreases (after 30 weeks of gestation age) which happens along with change of collagen concentration [43]. The different alignment and concentration of collagen causes the cervix to behave like a heterogeneous medium.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of cervical length provides an accurate prediction of risk for early preterm delivery (4). Transvaginal ultrasound scan (TVS) measurement has become the preferred method and is the only ultrasound technique that has been validated in the prediction of spontaneous preterm birth (5). Although TVS is the method that is generally recommended for assessing cervical length in women at high risk of preterm birth, many women in our culture either decline or are not happy to have a TVS during pregnancy.…”
Section: Introductionmentioning
confidence: 99%